Sikap Asertif Perawat dalam Memberikan Pelayanan Keperawatan di Instalasi Rawat Inap di Rumah Sakit - Rahmat Pannyiwi; Nurhaedah Nurhaedah; Andi Hariati (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; The era of globalization that is being and will be faced by us in the health sector raises a glimmer of hope for the opportunity to improve health services. Objectives; know the assertiveness of nurses in providing nursing services in inpatient installations at hospitals. Method; Descriptive research describes the level of education, work experience, and gender towards the assertiveness of nurses. Result; shows that verbal communication 38 (69.1%), non-verbal communication 39 (70.9%) and the factors that influence verbal and non-verbal communication 30 (54.5%). Conclusion; that in providing nursing services, nurses can show non-assertive behavior because it is influenced by several factors, for example, environmental factors. The interaction environment will affect effective communication.